Effect of B site substitution in Gd2B2-xNiyO7-delta (B= Ti, Zr) ternary metal oxide catalysts in dry reforming of methane - Ghodke, Seema R.; Thundiyil, Shibin; Dongapure, Pavan; Devi, R. Nandini (Molecular Catalysis, 2022)
Structured catalysts are emerging as active and durable catalysts in dry reforming of methane due to their inherent characteristics like lattice insertion of active metals and consequent stability imparted. Here we report Ti and Zr substituted Gd2B2-xNiyO7-delta (B = Ti, Zr) catalysts synthesized by citrate gel method, which are characterized and tested for dry reforming of methane. Structure and Ni substitution has been confirmed by Rietveld refinement of powder XRD patterns and Raman analysis. TPR and CO2-TPD were performed to analyze the reducibility and effect of basic sites of catalysts in DRM activity. Ni doped Ti analogue shows stable and superior activity towards dry reforming of methane for 100 h. The in situ IR studies and XPS analysis confirmed the presence of surface hydroxyl species in this catalyst, which triggers the activation of CO2 and provides higher and durable activity in dry reforming reaction. Absence of any C formation in this catalyst after durability test indicates the mechanism of C gasification by the surface hydroxyl species enhancing stable activity for long durations.
Keywords: A(2)B(2)O(7); Citrate gel method; Dry reforming of methane; Ternary metal oxide